2016
DOI: 10.1071/bt16105
|View full text |Cite
|
Sign up to set email alerts
|

Whole-chloroplast analysis as an approach for fine-tuning the preservation of a highly charismatic but critically endangered species, Wollemia nobilis (Araucariaceae)

Abstract: The critically endangered Wollemia nobilis W.G. Jones, K.D. Hill & J.M. Allen is endemic to Wollemi National Park north of Sydney (Australia). All known wild individuals are restricted to four sites in a single canyon system. W. nobilis can reproduce sexually but at all sites individual clumps can be multi-stemmed from a common base. In the first genetic study of this species, no genetic variation was found across multiple genetic marker types representing hundreds of nuclear loci, indicating this species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…A similar case is observed for the ancient relict Wollemi pine (Wollemia nobilis), a species with fewer than 100 extant wild trees. Until the recent discovery of three distinct chlorotypes (Greenfield et al 2017), no genetic diversity was detected in any extant W. nobilis plants (Peakall et al 2003). A single cutting could thereby represent 100% genetic capture of a wild population, and three cuttings could represent all known genetic diversity for the species.…”
Section: Can the Relative Size Of Populations Guidementioning
confidence: 99%
“…A similar case is observed for the ancient relict Wollemi pine (Wollemia nobilis), a species with fewer than 100 extant wild trees. Until the recent discovery of three distinct chlorotypes (Greenfield et al 2017), no genetic diversity was detected in any extant W. nobilis plants (Peakall et al 2003). A single cutting could thereby represent 100% genetic capture of a wild population, and three cuttings could represent all known genetic diversity for the species.…”
Section: Can the Relative Size Of Populations Guidementioning
confidence: 99%
“…However, following sequencing of the chloroplast genome (Yap et al, 2015), exceptionally low -yet detectable -genetic diversity was found in a whole-chloroplast analysis (Greenfield et al, 2016). More refined population genetic studies based on reduced representation genome sequencing approaches are ongoing but preliminary investigations 16 have identified low-level variation within and between subpopulations (Bragg et al, unpubl.).…”
Section: Genetic Variationmentioning
confidence: 99%
“…This lack of human contact is given as one of the reasons why specific trees within this enclave are estimated to be over 1000 years in age (Wong, 2019). Whilst this isolation has aided the species' survival, it has also limited the Wollemi in some ways: initial genetic studies of these ancient conifers originally revealed no genetic diversity in the small wild population that was spread across four close sites-an 'evolutionary bottleneck' (Greenfield, et al 2016;Peakall, et al 2003). More recent studies, however, demonstrate small genetic variations between specimens, but, given the Wollemi once covered a vast area of the Gondwanan supercontinent, these similarities in genetic material demonstrate that for extended periods the tree has existed in relative seclusion (Greenfield, et al 2016).…”
Section: Landscapes Of Vegetal Agencymentioning
confidence: 99%
“…Whilst this isolation has aided the species' survival, it has also limited the Wollemi in some ways: initial genetic studies of these ancient conifers originally revealed no genetic diversity in the small wild population that was spread across four close sites-an 'evolutionary bottleneck' (Greenfield, et al 2016;Peakall, et al 2003). More recent studies, however, demonstrate small genetic variations between specimens, but, given the Wollemi once covered a vast area of the Gondwanan supercontinent, these similarities in genetic material demonstrate that for extended periods the tree has existed in relative seclusion (Greenfield, et al 2016). The continued survival of the Wollemi is phenomenal in a time when plant growth has been reduced by half from the beginning of human civilisation (Bar-On, Phillips and Milo, 2019).…”
Section: Landscapes Of Vegetal Agencymentioning
confidence: 99%